Disney Pixar Cars - Smiley, Ben.; Orpinas, Jean-Paul.; Tilley, Scott.; Posner-Sanchez, Andrea.; Estudi, Ivan Boix.; Luckey, Bud, 1934-; Louis, Dominique. (Golden books., 2011)
Three stories from the Disney and Pixar motion pictures Cars.